Digital Objects: The Legal Peculiarities, the Role and Prospects of Use - Okriashvili, Timur Giorgievich; Valer’evich, Voronin Maksim; Pavlyuk, Albert Valentinovich; Kirillova, Elena Anatolyevna (Cuestiones Políticas, 2020)
Digital assets are increasingly used in civil invoicing, which requires the development and unification of legal standards in the field of the creation and use of digital assets. The main objective of this study is to define digital assets as a legal category and precisely characteristics for the digital objects of other civil objects according to identifications. Methods of analysis of legal standards, collection and study of individual facts, statistical methods, scientific abstraction methods and methods of representation of the archives were used. The study that digital objects are an independent legal category, which is an intangible digital asset that can only be created with the help of modern technologies, my that ownership of digital objects arises from the moment of verification with a verification with a code and the realization of a digital input. in a special transaction log. For the right of inheritance of digital objects, it is necessary to implement a verification of holder verification and identification of digital objects during their creation and disposal.